Training and support for caring for a child's gastrostomy: a survey with family carers. Issue 1 (27th July 2021) - Page, Bethan; Butler, Siobhan; Smith, Colette; Lee, Alex CH; Vincent, Charles A
Abstract : Objective: The aim of this study was to explore family carers' experiences of training and ongoing support for caring for their child's gastrostomy, and to get their views on how this could be improved. Methods: A mixed-methods online survey with 146 family carers (eg, parents, grandparents) who care for a child with a gastrostomy. Family carers rated their own experience of training and support and made recommendations for how training and support could be improved for future families. Results: The nature and extent of the training family carers reported receiving varied considerably. Many felt that the demonstrations they received in hospital were too brief. Two in five family carers rated their confidence caring for their child's gastrostomy as very low in the first few weeks after surgery. Parents valued ongoing learning and support from other parents and support from community nurses. Videos and simulation practice were rated as useful formats of training, in addition to face-to-face supervised practice with a clinician. Parents liked how real life the example video shown was, and rated nearly all suggested video topics as 'very helpful', especially troubleshooting topics. Conclusions: Our study found substantial variability in family carers' descriptions of the training and support they received to care for their child's gastrostomy. Training often did not meet family carers' needs. We need to invest in better training and support for families and learn from their recommendations. Improvements to training and support for families (eg, through instructional videos) have the potential to improve family carers' confidence and competence, and reduce the risk of problems and complications which cause harm to children and increase demand on National Health Service (NHS) resources.